New Challenges to Ageing in the Rural North A Critical Interdisciplinary Perspective - Naskali, Päivi; Harbison, Joan R.; Begum, Shahnaj; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides an underexplored view of ageing, one that conceives older people as valuable resources in their communities, as active citizens with both voice, and an agency that includes the capacity for resistance. It acknowledges that becoming old with dignity means also paying attention to caring, good health services and the possibility of good death. The book defines age and ageing as multiple, culturally and historically constructed phenomena that are only loosely connected to the years of one's life. In focusing on the peripheral North located in the Nordic, Canadian and Russian north, it highlights important questions and viewpoints that can be found and adapted to other rural areas. The book answers the following questions: What is the relevance of legislation and international legal agreements in ensuring the rights of elderly people under political and economic changes? What challenges do geographic isolation, changing age structure, and cultural and ecological transformations pose to possibilities for meeting older people's needs for engagement in society as well as for their care? As such this book will be of interest to all those working in population aging.
Part I. Changing Politics and Welfare Policies in the North -- Chapter 1. CEDAW and the Capability Approach as a Way to Promote Elderly Women in the North(Eva-Maria Svensson) -- Chapter 2. Gender Equality and Ageing in Arctic Sweden(Lena Wennberg) -- Chapter 3. Elder Care Policy and Service System in Phase of Transition in Finland(Heli Valokivi) -- Chapter 4. New Opportunities Telling the Same Frustrating Story Care Sector Marketization and Innovations in Finland(Petra Merenheimo) -- Part II. Challenges in Meeting Older People's Needs in the Northern Rural Context -- Chapter 5. Approaches to Prevent Social Exclusion of Older Adults in Arctic Russian Remote Area(Anastasia Emelyanova & Elena Golubeva) -- Chapter 6. Social Cultural Construction of Dying Self in the Context of Care(Marjo Outila, Marjaana Seppänen, Heli Valokivi, Eeva Rossi) -- Chapter 7. Exploring Challenges to Elderly in a Rural Settings: A Case Study from Finnish Lapland(Shahnaj Begum) -- Chapter 8. Hit by the Stroke - AnAuto-Ehnographic Analysis of Caring Old Parents from Long Distance(Marit Aure) -- Chapter 9. Individually but Together: Old Couple Preparing for Old Age(Olga Asrun Stefansdottir & Eydis Kristin Sveinbjarnardottir) -- Chapter 10. Social Inclusion and Agency of Older Women in Rural Tornedalen, North Sweden(Tarja Tapio) -- Part III. Age, voice and resistance -- Chapter 11. "Are We Really Listening"? Ageism, Voice, and Older People's Diversity in Nordic Societies Undergoing Welfare Change(Joan R. Harbison) -- Chapter 12. From "active ageing" to Local Perspectives on Quality of Life(Mai Camilla Munkejord, &Walter Schönfelder) -- Chapter 13. Elderly people as political actors in Lapland(Päivi Naskali) -- Chapter 14. "We do not eat luxury food" A story about health and food in the everyday life of an elder Sami reindeer herder in Norway(Trine Kvitberg) -- Conclusion.
Keywords: Aging; Ageing